CORPORATE DIVERSIFICATION AND PERFORMANCE - Wan Daud, Wan Mohd Nazri; Salamudin, Norhana; Ahmad, Ismail (International Business Education Journal, 2009)
Business diversification has drawn attention of strategic management and finance scholars.  This study examines relationship between diversification effect on performance using multiple measures of performance namely accounting and market measurements. The study used panel data analysis for a sample of 70 Malaysian firms from various industries during the period 2001 to 2005.The evidence produces some interesting findings with regard to risk factors and effect on firm’s performance while other factors are consistent with previous findings. In particular, firms that adopt the focused strategy perform better than those with diversified strategy. Different measures of performance used in the study produces varying results after controlling for risk, firm size and economic condition, using inflation rate as a proxy.